What drives women into entrepreneurial activities? view from Malaysia and Philippines - Merlinda Muharam, Farrah; C. Israel, Marietta; Ai Chin, Thoo; Sulaiman, Zuraidah; Abu Talib, Noraini; Haiyat Abdul Kohar, Umar; A. Meneses, Benita; O. Daval Santos, Eliza (International Journal of Engineering and Technology, 2018)
Women nowadays are actively involved in entrepreneurship and contributing to economy development. In developing country such as Malaysia and Philippines, the participations are increasingly noted, yet the phenomena are still new. This study aims to understand the factors that motivate women to involve in entrepreneurship, in addition to their profiles and industry/business engagement. The study further explores the obstacles faced before/during venturing into entrepreneurial activities. Using quantitative approach, descriptive method and correlation are used to understand the phenomena. Findings from this study will provide a profiling of women entrepreneurs together with their motivational factors and to understand the challenges faced in the course. As both countries are establishing women as part of their economic development player, this study shall provide real inputs for policy building in promoting, encouraging and easing women involvement in entrepreneurial activities and the related industry.Â Â